ANALISIS FAKTOR-FAKTOR YANMG MEMPENGARUHI KEPUASAN MASYARAKAT PADA PELAYANAN BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG - Fardhani, Harentama; Rahardjo, Muji (Jurnal Analisis Bisnis Ekonomi, 2010)
This research analysed the influence of service as a factor affecting people satisfaction. According to Kepmen PAN No. 25 in 2004 on the Public Satisfaction Index (IKM), there are 14 matters relating to the performance and services carried out by employees of service, including service procedures, compliance requirements, clarity of employees, employee discipline, employee responsibilities, capabilitiers of staff, speed of service, justice services, staff courtesy, fairness of costs, certainty of cost, schedule certainly, comfort environments, and security services. This research was conducted to analyze the value of these variables, and effect on community satisfaction. Through IKM counting, could be learnt the value of the index was 3.180 and the IKM value after being converted of 79.6. Was based on this IKM value, could be concluded by the quality of the Badan Pelayanan Perijinan Terpadu (BPPT) of Semarang city entered the good criterion. Through factor analysis, 14 indicators of service has been reduced to 8 indicators are then grouped into two factors, namely the quality factors and services procedures factor. Through the analysis of regression, could be known that the quality factor of the service and the influential factor of the service procedure significant towards the people's satisfaction.